HASIL IMPLEMETASI METODE GAME PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP MINAT BELAJAR SISWA PADA KELAS VII DI SLB CG YPPCG BINA SEJAHTERA SURAKARTA TAHUN 2022/2023 - Mohamad Ariansah Thalib; Joko Sarjono; P Praptiningsih; Meti Fatimah (MAMBA'UL 'ULUM, 2023)
This study aims to determine the use of the game method. This research is a qualitative research. The subject of the study was SLB CG-YPPCG Bina Sejahtera Surakarta. In this study, data collection methods were used through observation, interviews, and documentation. Meanwhile, data analysis uses data reduction, data presentation, and data verification. The results show that the characteristics of students at SLB CG-YPPCG Bina Sejahtera Surakarta are experiencing slowness in doing something or difficulty in understanding and learning new things. Then the game method used in learning is that the teacher provides learning with an arrangement of simple and sequential steps made with simple and fun games. So with this model learning can improve social and motor skills for mentally retarded children at SLB CG-YPPCG Bina Sejahtera Surakarta.